Investigation of effect of binder on next generation cathode performance in lithium-ion batteries - Tang, Ernest Jun Jie (Nanyang Technological University, 2024)
Energy dense lithium-ion batteries (LIB) have garnered increased interest, especially in light of the growing demand for applications, such as electric vehicles. While the adoption of high-nickel cathode materials, such as LiNi0.6Mn0.2Co0.2O2 (NMC622), presents a promising approach for attaining high energy density, the intrinsic complexity of the LIB leads to variations in its electrochemical performance and stability, influenced by numerous factors. Recent research focus now prioritizes the fabrication process of electrodes due to its consequential influence on the electrochemical performance of the electrode. Typically, the manufacturing of LIBs cathodes employ polyvinylidene fluoride (PVDF), as a binder. This study aims to elucidate the implications of mixing process on slurry rheology and the subsequent electrochemical properties of the coated cathode for LIB. Various key factors including solid content, mixing speed, and duration significantly impact the slurry rheological properties, subsequently impacting the coating quality. Through analyzing the physical appearance of the coating and an in-depth exploration of surface morphology, the correlation between rheological properties and electrochemical performance is potentially bolstered. Furthermore, preliminary studies of commercial batteries were undertaken to investigate the implications of employing different binders on battery electrochemical performance. Innovative techniques were employed to recycle waste PVDF as a binder, presenting a sustainable pathway for electrode fabrication that sheds light on the essential role binders play in a closed-loop manufacturing of batteries. This study could provide future researchers guidance on developing sustainable manufacturing of batteries with excellent electrochemical properties.